2015
DOI: 10.1007/s12206-015-0828-0
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Melting of nanoparticles-enhanced phase change material (NEPCM) in vertical semicircle enclosure: numerical study

Abstract: Convection melting of ice as a Phase change material (PCM) dispersed with Cu nanoparticles, which is encapsulated in a semicircle enclosure is studied numerically. The enthalpy-based Lattice Boltzmann method (LBM) combined with a Double distribution function (DDF) model is used to solve the convection-diffusion equation. The increase in solid concentration of nanoparticles results in the enhancement of thermal conductivity of PCM and the decrease in the latent heat of fusion. By enhancing solid concentration o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…The authors indicated that the Lorentz force, caused by the Hartmann number, and buoyancy forces had positive and negative impacts on the solidification rate of nanoparticle-enhanced PCMs, respectively. Jourabian et al [31] utilised the enthalpy-based Lattice Boltzmann method and double distribution function to explore the melting process of the ice within a semicircle enclosure. The authors noticed that the concentration of nanoparticles had a positive and an adverse effect on the thermal conductivity and the latent heat of PCMs, respectively, but a negligible impact on the average Nusselt number.…”
Section: Introductionmentioning
confidence: 99%
“…The authors indicated that the Lorentz force, caused by the Hartmann number, and buoyancy forces had positive and negative impacts on the solidification rate of nanoparticle-enhanced PCMs, respectively. Jourabian et al [31] utilised the enthalpy-based Lattice Boltzmann method and double distribution function to explore the melting process of the ice within a semicircle enclosure. The authors noticed that the concentration of nanoparticles had a positive and an adverse effect on the thermal conductivity and the latent heat of PCMs, respectively, but a negligible impact on the average Nusselt number.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, knowing the fact that the PCMs have low thermal conductivity by instinct, which extremely affects the thermal performance in thermal energy systems, many investigators have tried to increase the overall thermal performance of the systems implementing several methods, such as using porous metal foams [3,4,5,6], metal matrix [7], fin [8,9,10,11], and nanoparticles dispersed into the PCMs [12,13,14,15], and nano-encapsulation PCMs [16,17,18,19]. Since nanoparticles play a promising role in enhancing the thermal performance of multifarious systems, the mixture of PCM and nanoparticles to produce Nano-enhanced Phase Change Materials (NePCM) has been extensively investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Figure12. Variation of the total heat transfer (left) and total heat transfer ratio (right) with the volume fraction of NEPCMs, interface heat transfer parameter and the thermal conductivity of the porous matrix (Ste ¼ 0.2 and θ f ¼ 0.5).…”
mentioning
confidence: 99%
“…In contrast, the lattice Boltzmann (LB) model with the volumetric LB scheme can avoid the empirical mushy zone constant with no free parameters when it is used for simulating the melting process [23,24]. The evolution of temperature and mushy zone by using the lattice Boltzmann method (LBM) was investigated in various cavities such as square cavity [25][26][27], semicircle enclosure [28], an annulus between two coaxial vertical cylinders [29], and more complex structures [30,31].…”
Section: Introductionmentioning
confidence: 99%